Efek tepung ulat sagu (Rhynchophorus ferrugineus) terhadap penurunan kadar malondialdehyde (MDA) pada tikus Wistar dengan diet rendah protein - Lara Ayu Lestari; M. Sulchan; Anang M Legowo; Kusmiyati Tjahjono; Achmad Zulfa Juniarto (Jurusan Gizi Politeknik Kesehatan Kemenkes Aceh, 2021)
Kwashiorkor is protein-energy malnutrition (PEM) caused by protein deficiency. Sago worm flour (Rhynchophorus ferrugineus) can reduce malondialdehyde (MDA) caused by the high content of the amino acids glycine, lysine, and phenylalanine. The study aimed to prove the effect of sago worm flour on MDA levels in Wistar rats with a low protein diet. A true experimental-pre-post control group. The intervention was given for 28 days to 28 Wistar rats, divided into four groups with each group of seven rats. The dose of sago starch was 0,36 g/100 g rat body weight/day (P1), and a dose of 1,36 g/100 g rat body weight/day (P2) for rats fed a low diet protein. The treatment group was compared with a group of mice given a low diet protein (K +) and a group of healthy mice (K-). Serum MDA levels were measured by the TBARs method. Statistical analysis used paired t-test or Wilcoxon test and one-way ANOVA/Kruskal Wallis test. The results of decreasing MDA levels were in the P1 and P2 groups (p= 0,000). There was a difference in MDA levels in the P1 and P2 groups compared to the K + group (P= 0,000). There was a difference that decreased MDA levels between P1 and P2 (p= 0,000). In conclusion, sago worm flour at a dose of 0,36 g/100 g of rats/day and a dose of 1,36 g/100 g of body weight of rats/day can reduce MDA levels